Looking on the Bright Side of Livestock Emotions—the Potential of Their Transmission to Promote Positive Welfare - Baciadonna, Luigi; Duepjan, Sandra; Briefer, Elodie F.; Padilla de la Torre, Monica; Nawroth, Christian (Frontiers in Veterinary Science, 2018)
Emotions can be defined as an individual’s affective reaction to an external and/or internal event that, in turn, generates a simultaneous cascade of behavioural, physiological, and cognitive changes. Those changes that can be perceived by conspecifics have the potential to also affect other’s emotional states, a process labelled as “emotional contagion”. Especially in the case of gregarious species, such as livestock, emotional contagion can have an impact on the whole group by, for instance, improving group coordination and strengthening social bonds. We noticed that the current trend of research on emotions in livestock, i.e. investigating affective states as a tool to assess and improve animal welfare, appears to be unbalanced. A majority of studies focuses on the individual rather than the social component of emotions. In this paper, we highlight current limitations in the latter line of research and suggest a stronger emphasis on the mechanisms of how emotions in livestock are transmitted and shared, which could serve as a promising tool to synergistically enhance the welfare of all individuals within a group.